2008
DOI: 10.1074/jbc.m709581200
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of UDP-N-acetylglucosamine Is Essential for Bloodstream Form Trypanosoma brucei in Vitro and in Vivo and UDP-N-acetylglucosamine Starvation Reveals a Hierarchy in Parasite Protein Glycosylation

Abstract: A gene encoding Trypanosoma brucei UDP-N-acetylglucosamine pyrophosphorylase was identified, and the recombinant protein was shown to have enzymatic activity. The parasite enzyme is unusual in having a strict substrate specificity for N-acetylglucosamine 1-phosphate and in being located inside a peroxisome-like microbody, the glycosome. A bloodstream form T. brucei conditional null mutant was constructed and shown to be unable to sustain growth in vitro or in vivo under nonpermissive conditions, demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 57 publications
4
81
0
Order By: Relevance
“…3B) and TbUGGT null mutant (Fig. 3C) profiles both show the same range of glycoforms that arise from the known heterogeneity in the GPI anchor (42) and N-glycans (70) of this particular VSG (29,39,62,67) (Table 2). Thus, we may conclude that there is no alteration in the glycosylation pattern of mature VSG expressed in the TbUGGT null mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B) and TbUGGT null mutant (Fig. 3C) profiles both show the same range of glycoforms that arise from the known heterogeneity in the GPI anchor (42) and N-glycans (70) of this particular VSG (29,39,62,67) (Table 2). Thus, we may conclude that there is no alteration in the glycosylation pattern of mature VSG expressed in the TbUGGT null mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the oligomannose-containing C-terminal Asn428 site of VSG221 may be in a domain that does not need help with folding, whereas the Man 5 GlcNAc 2 -containing N-terminal Asn263 site is reversibly glucosylated in this glycoprotein. Interestingly, under UDP-GlcNAc starvation conditions, T. brucei produces two major species of VSG221; one form contains both Cterminal and N-terminal N-linked glycans, whereas the other form contains only the N-terminal glycan, whose precursor is Man 5 GlcNAc 2 (29,62). Underglycosylation of the Asn486 site, but not of the Asn263 site, is also seen in the T. brucei ALG3 mutant (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, UDP-galactose is essential in both bloodstream and procyclic forms T. brucei and also appears to be essential in T. cruzi (25,42,43), GDP-mannose is essential for infectivity in Leishmania major and survival in T. brucei (9,10), and UDP-GlcNAc is essential for L. major pathogenesis in the mammalian host (34) and the growth and survival of bloodstream-form T. brucei (46).…”
mentioning
confidence: 99%
“…This may explain why GalNAc has yet to be found in any glycoconjugates of this parasite. (b) All the enzymes identified in the biosynthesis of the above five nucleotide sugars were localized to the glycosomes (44,46,59,(61)(62)(63), which are microbodies evolutionarily related to peroxisomes in higher eukaryotes and their function is essential in carbohydrate metabolism in T. brucei. However, in its mammalian hosts, most nucleotide sugars are synthesized in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that enzymes involved in nucleotide sugar biosynthesis in T. brucei such as UDP-Gal (59,61,78), GDP-Fuc (62), GlcNAc (63), and GDP-Man are essential for cell growth, but none of them were shown to cause pathogenicity changes in BSF T. brucei. We speculate that the function of the totality of TbNSTs is essential for cell growth and that inhibition of a specific or multiple tbnst involved in glycosylation of essential proteins for virulence will change the parasites' infectivity.…”
Section: Discussionmentioning
confidence: 99%